2013
DOI: 10.1021/jp4063687
|View full text |Cite
|
Sign up to set email alerts
|

Following the Thermal Activation of Au25(SR)18 Clusters for Catalysis by X-ray Absorption Spectroscopy

Abstract: We show the thermal activation of phenylethanethiolate (L = SC 8 H 9 ) and hexanethiolate (L = SC 6 H 13 )A u 25 L 18 monolayer protected clusters (MPCs) on carbon black supports, followed by characterization with extended Xray absorption fine structure (EXAFS) spectroscopy and transmission electron microscopy (TEM). EXAFS analysis shows that the thiolate stabilizers can be partially removed from the surface under mild heating conditions without significant changes in the cluster size. The resulting clusters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
103
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 48 publications
9
103
0
Order By: Relevance
“…Similar studies with Au/Ag clusters have been reported by other earlier workers. 29,46,47 Our experiments …”
Section: Catalytic Activity Of Au-zno Nanocompositesmentioning
confidence: 90%
“…Similar studies with Au/Ag clusters have been reported by other earlier workers. 29,46,47 Our experiments …”
Section: Catalytic Activity Of Au-zno Nanocompositesmentioning
confidence: 90%
“…23,24 When metal nanoclusters are used as catalysts, appropriate supports are usually needed to not only improve their dispersity but also enhance the stability. Among the materials, carbon and transition metal oxides are most widely used as supports.…”
Section: Introductionmentioning
confidence: 99%
“…Such structural information is crucial for identifying and further understanding the catalytically active locations on the surface of the metal NP or NC. A study by Shivhare et al demonstrated that partially or completely removing the protecting ligands from alkanethiolate-protected Au 25 NCs (supported on carbon powder) by calcination increased the catalytic reduction of 4-nitrophenol [51]. Au L 3 -edge EXAFS spectra for Au 25 (SC 8 H 9 ) 18 and Au 25 (SC 6 H 13 ) 18 were collected before thermal treatment and fitted using four shells to confirm the core and surface local structure of the NC samples.…”
Section: Introduction To Gold Nanoclustersmentioning
confidence: 99%